Prácticas éticas de los servidores administrativos y su incidencia en la calidad y calidez de atención en la Unidad Educativa José Rodríguez Labandera, del cantón Quevedo, año 2017 - Bustamante Avilés, Dora Del Pilar (2017)
The main objective of this thesis work is the implementation of ethical practices of administrative servants and their impact on the quality and warmth of attention in the Educational Unit "José Rodríguez Labandera", Del Cantón Quevedo, Year 2017. For this purpose , it was based on an analysis of the shortcomings that the administrative servants have in this educational institution with respect to the form of attention to the user and community in general, this research puts a lot of interest in the subject so that those who make up the entity under study they can develop an excellent quality and warmth in the attention, since being this is not only necessary the organization but also in the daily activities, so for the obtaining of the data on the problem a survey was carried out in the institution directed to the users, the same ones who expressed their realities, also the results obtained from the bib review liográfica allowed to elaborate a proposal as a methodological tool for administrative servants of the campus in force.